The Geometries and Stabilities of Neutral and Anionic Vanadium-Doped Germanium Clusters VGen0/-(n = 9 - 13): A Density Functional Theory Investigation - Huu Tho, Nguyen; Tu, Trang Thanh; Nhan, Trac Minh; Cam, Pham Hong; Thi, Pham Thi (VNU Journal of Science: Natural Sciences and Technology, 2019)
The geometries and stabilities of VGe n 0/- (n = 9 - 13) clusters were systematically studied with the density functional theory (DFT) using the BP86 functional and LANL2DZ basis set. Several possible multiplicities of each cluster were tested to determine the most stable structure among the isomers. The average binding energy per atom, fragmentation energy, second order energy difference and HOMO-LUMO gaps were evaluated. The results indicate that the neutral and anionic clusters possessed higher stability when n = 10 and 12. The vertical detachment energy (VDE) and adiabatic detachment energy (ADE) were also calculated for anionic clusters to investigate their stabilities. Among the neutral clusters, VGe 10 had both the highest vertical ionization potential (VIP) and chemical hardness. Keywords BP86/LANL2DZ, binding energy, VGe n 0/- clusters, structure of clusters. References [1] Shunping Shi, Yiliang Liu, Chuanyu Zhang, Banglin Deng, Gang Jiang, A Computational Investigation of Aluminum-doped Germanium Clusters by Density Functional Theory Study, Computational and Theoretical Chemistry, 1054 (2015) 8-15. https://doi.org/10.1016/j.comptc. 2014.12.004. [2] Wen-Jie Zhao, Yuan-Xu Wang, Geometries, stabilities, and Magnetic Properties of MnGen (n = 2-16) Clusters: Density-functional Theory Investigations, Journal of Molecular Structure: THEOCHEM, 901 (1–3) (2009) 18-23. https://doi.org/10.1016/j.theochem.2008.12.039. [3] Shi Shun-Ping, Liu Yi-Liang, Deng Bang-Lin, Zhang Chuan-Yu, and Jiang Gang, Density Functional Theory Study of The Geometrical and Electronic Structures of (n = 1 - 9) clusters, World Scientific Publishing Company, 30 (2016) 1750022-1750039. https://doi.org/10. 1142/S0217979217500229. [4] J.Stato, H.Kobayashi, K. Ikarashi, N.Saito, H.Nishiyama, and Y. Inoue, Photocatalitic Activity for Water Decomposition of RuO2-Dispersed Zn2GeO4 with d10 Configuration, The Journal of Physical Chemistry B, 108 (14) (2004) 4369-4375. DOI: 10.1021/jp0373189. [5] Daoxin Dai, Molly Piels, and John E. Bowers, Monolithic Germanium/Silicon Photodetectors With Decoupled Structures: Resonant APDs and UTC Photodiodes, IEEE Journal of Selected Topics in Quantum Electronics, 20 (6) (2014) 3802214-3802227. DOI: 10.1109/JSTQE.2014. 2322443 [6] C. Y. Chou, G. S. Hwang, On The Origin of The Significant Difference in Lithiation Behavior Between Silicon and Germanium, Journal of Power Sources, 263, (2014) 252-258. https://doi.org/10.1016/j.jpowsour.2014.04.011. [7] Siwen Zhang, Bosi Yin, Yang Jiao, Yang Liu, Xu Zhang, Fengyu Qu, Ahmad Umar, Xiang Wu, Ultra-long Germanium Oxide Nanowires: Structures and Optical Properties, Journal of Alloys and Compounds, 606 (2014) 149-153. https://doi.org/10.1016/j.jallcom.2014.03.171. [8] T. Herrmannsdörfer, V. Heera, O. Ignatchik, M. Uhlarz, A. Mücklich, M. Posselt, H. Reuther, B. Schmidt, K.-H. Heinig, W. Skorupa, M. Voelskow, C. Wündisch, R. Skrotzki, M. Helm, and J. Wosnitza, Superconducting State in a Gallium-Doped Germanium Layer at Low Temperatures, Physical Review Letters, 102 (2009) 217003-217006. DOI: 10.1103/PhysRev Lett.102.217003. [9] Vijay Kumar, and Yoshiyuki Kawazoe, Metal-Encapsulated Caged Clusters of Germanium with Large Gaps and Different Growth Behavior than Silicon, Physical Review Letters, 88 (2002) 235504-235507. DOI: 10.1103/PhysRevLett.88. 235504. [10] Xiao-Jiao Deng, Xiang-Yu Kong, Hong-Guang Xu, Xi-Ling Xu, Gang Feng, and Wei-Jun Zheng, Photoelectron Spectroscopy and Density Functional Calculations of VGen- (n = 3 − 12) Clusters, The Journal of Physical Chemistry C, 119 (20) (2015) 11048-11055. https://pubs.acs. org/doi/10.1021/jp511694c. [11] J. P. Perdew, K. Burke, M. Ernzerhof, Generalized Gradient Approximation Made Simple, Physical Review Letters, 77 (1996) 3865-3868. https://doi.org/10.1103/PhysRevLett.77.3865 [12] Chaouki Siouani, Sofiane Mahtout, Sofiane Safer, and Franck Rabilloud, Structure, Stability and Electronic and Magnetic Properties of VGen (n = 1-19) Clusters, The Journal of Physical Chemistry A, 121 (18) (2017) 3540-3554. https://pubs.acs. org/doi/abs/10.1021/acs.jpca.7b00881. [13] Jin Wang, and Ju-Guang Han, A Theoretical Study on Growth Patterns of Ni-Doped Germanium Clusters, The Journal of Physical Chemistry B, 110 (15) (2006) 7820-7827. https://pubs.acs.org/doi/abs/10.1021/jp0571675 [14] Debashis Bandyopadhyay and Prasenjit Sen, Density Functional Investigation of Structure and Stability of Gen and GenNi (n = 1 − 20) Clusters: Validity of the Electron Counting Rule, The Journal of Physical Chemistry A, 114 (4) (2010) 1835-1842. https://pubs.acs.org/doi/abs/10.1021 /jp905561n. [15] Soumaia Djaadi, Kamal Eddine Aiadi, and Sofiane Mahtout, Frist Principles Study of Structural, electronic and magnetic properties of (n=1-17) clusters, Journal of Semiconductors, 39 (4) (2018) 42001-420013. https://doi.org/10.1088/1674-4926/39/4/042001. [16] İskender Muz, Mustafa Kurban, Kazım Şanlıc, Analysis of the Geometrical Properties and Electronic Structure of Arsenide Doped Boron Cluster: Ab-initio approach, Inorganica Chimica Acta, 474 (2018) 66-72. https://doi.org/10.1016/ j.ica.2018.01.030. [17] A. D. Becke, Density-functional exchange - energy approximation with correct asymptotic behavior, Physical Review A, 38 (1988) 3098-3100. https://doi.org/10.1103/PhysRevA.38.3098 [18] W. R. Wadt, P. J. Hay, Ab initio effective core potentials for molecular calculations. Potentials for main group elements Na to Bi, The Journal of Chemical Physics, 82 (1) (1985) 284-298. https://doi.org/10.1063/1.448800. [19] W. R. Wadt, P. J. Hay, Ab initio effective core potentials for molecular calculations. Potentials for K to Au including the outermost core orbitals. The Journal of Chemical Physics, 82 (1) (1985) 299-310. https://doi.org/10.1063/1.448975. [20] W. R. Wadt, P. J. Hay, Ab initio effective core potentials for molecular calculations. Potentials for the transition metal atoms Sc to Hg. The Journal of Chemical Physics, 82(1) (1985) 270-283. https://doi.org/10.1063/1.448799. [21] Gabriele Manca, Samia Kahla, Jean-Yves Saillard, Rémi Marchal, Jean-François Halet, Small Ligated Organometallic Pdn Clusters (n = 4 - 12): A DFT Investigation, Journal of Cluster Science, 28 (2) (2017) 853-868. https://doi.org/ 10.1007/s10876-017-1168-2. [22] Tran Dieu Hang, Huynh Minh Hung, Lam Ngoc Thiem. M. T. Nguyen Hue, Electronic structure and thermochemical properties of neutral and anionic rhodium clusters Rhn, n = 2 – 13. Evolution of structures and stabilities of binary clusters RhmM (M = Fe, Co, Ni; m = 1 – 6). Computational and Theoretical Chemistry, 1068 (2015) 30–41. https://doi.org/10.1016/j.comptc. 2015.06.004. [23] J. M. Frisch, et al. (2010). Gaussian 09, Revision C.01.Gaussian, Inc., Wallingford CT.